Social Values for Ecosystem Services (SolVES): Open-source spatial modeling of cultural services. (February 2022) - Sherrouse, Benson C.; Semmens, Darius J.; Ancona, Zachary H.
Abstract: Social Values for Ecosystem Services (SolVES) version 4.0 is a fully open-source, GIS-based tool designed to aid in the creation of quantitative, spatially explicit models of the nonmonetary values attributed to cultural ecosystem services, such as aesthetics and recreation, specifically to facilitate their incorporation into larger ecosystem service assessments. Newly redeveloped for QGIS, SolVES can be applied in a wide variety of biophysical and social contexts including mountain, forest, coastal, riparian, agricultural, and urban settings worldwide. Redeveloping SolVES for an open-source platform was intended to expand its user base by eliminating the cost of proprietary GIS software licenses and to remove the impact of proprietary software changes on SolVES development. Providing additional options would enable users to delineate relevant stakeholder groups to better assess how differing preferences impact the intensity and spatial distribution of perceived social values. Highlights: SolVES creates spatially explicit models of cultural ecosystem service values. SolVES has been applied in a variety of ecosystem contexts around the globe. SolVES 4.0 has been redeveloped for QGIS. The open-source platform will help to expand the user base. Future development would enhance users' ability to delineate stakeholder groups.